Productive failure and learning through argumentation: Building a bridge between two research traditions to understand the process of peer learning. Issue 4 (20th October 2022) - Larrain, Antonia; Grau, Valeska; Barrera, María José; Freire, Paulina; López, Patricia; Verdugo, Sebastián; Gómez, Marisol; Ramírez, Francisca; Sánchez, Gabriel
ABSTRACT: Empirical evidence demonstrates the effect of productive failure (Kapur, 2008) on disciplinary knowledge. However, there is no clear theoretical explanation for why this is the case. Empirical evidence on argumentation and education shows the impact of curricular embedded deliberative argumentation on learning. However, these two trends of research have been mainly isolated, with insufficient synergy. Through the analysis of a group of sixth-graders collaborating around problems of natural selection, the aim of this paper is the theoretical exploration of the process of learning in productive failure designs through a focus on argumentative peer dialogue. The paper proposes an articulation of these two fields of research (productive failure and argumentation), which sheds light on both the learning dynamics in productive failure settings and the relevant insights for argumentative designs. The new possibilities for empirical research on learning through peer interaction opened up by these interconnected fields of research are proposed and discussed.